Vous êtes sur la page 1sur 1

# CALCUL ALGEBRIC

EXERCIŢII 1

1. (x + 6)·(x – 3) – (x – 5)·(x – 3) =
2. (x + 6)·(x – 4) – (x – 7)·(x – 7) =
3. (x – 7)·(x – 3) – (x + 7)·(x – 1) =
4. (x – 2)·(x – 2) – (x + 7)·(x – 8) =
5. (x – 2)·(x – 2) – (x + 4)·(x – 3) =
6. (6x + 4)·(x – 7) – (x – 7)·(6x – 2) =
7. (7x + 3)·(x – 4) – (x – 5)·(7x – 5) =
8. (5x + 6)·(x – 7) – (x – 4)·(5x – 5) =
9. (x + 8)·(6x – 5) – (x – 2)·(6x – 4) =
10. (x + 3)·(7x – 3) – (x – 3)·(7x – 4) =
11. (x + 2)·(5x – 8) – (x – 4)·(5x – 1) =
12. (2x + 5)·(6x – 6) – (4x – 7)(3x – 3) =
13. (2x + 6)·(6x – 5) – (4x – 2)·(3x – 4) =
14. (2x + 6)·(6x – 2) – (4x – 4)·(3x – 6) =
15. (8x + 2)·(3x – 5) – (4x – 4)·(6x + 2) =
16. (8x + 6)·(3x – 6) – (4x – 4)·(6x + 7) =
17. (8x + 5)·(3x – 3) – (4x – 1)(6x + 2) =
18. (x + 4)2 – (x – 4)·(x + 4) =
19. (x + 6)2 – (x – 7)·(x + 6) =
20. (x + 6)2 – (x – 4)·(x + 6) =
21. (x – 8)2 – (x – 4)·(x – 7) =
22. (x – 5)2 – (x – 2)·(x – 7) =
23. (x – 6)2 – (x – 5)·(x – 1) =
24. (x + 4)·(x – 3) – (x – 4)2 =
25. (x + 4)·(x – 6) – (x – 5)2 =
26. (x + 4)·(x – 3) – (x – 7)2 =
27. (4x + 1)2 – 16·(x – 8)·(x + 6) =
28. (2x + 4)2 – 4·(x – 2)·(x + 6) =
29. (5x + 4)2 – 25·(x – 5)·(x + 7) =

## Răspuns 1) 11x-33; 2) 16x-73; 3) -16x+28; 4) -3x+60; 5) -5x+16; 6) 6x-42; 7) 15x-37;

8) -4x-62; 9) 59x-48; 10) 43x-21; 11) 23x-20; 12) 51x-51; 13) 48x-38; 14) 68x-36; 15)
-18x-2; 16) -34x-8; 17) -11x-13; 18) 8x+32; 19) 13x+78; 20) 10x+60; 21) -5x+36; 22)
-1x+11; 23) -6x+31; 24) 9x-28; 25) 8x-49; 26) 15x-61; 27) 40x+769; 28) 0x+64; 29)
-10x+891;